Analysis of the Implementation of Planning, Implementation, Supervision, Administration, and Accountability of Village Fund Allocation - Ais Fauziah; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the implementation of planning, implementation, supervision, administration, and accountability of village fund allocations (study in Gunung Gangsir Village, Beji District, Pasuruan Regency). The sampling method used is qualitative research and is included in descriptive analysis research. The research location is in the Gunung Gangsir Village Government, Beji District, Pasuruan Regency, East Java Province. The data collection that was carried out were interviews, documentation, and observations. Test the validity of the data carried out in this study using the Triangulation Test. Activities in data analysis in this study are data collection, data reduction, data display, and conclusion drawing/verification. The results of this study indicate that Based on the results of the study, it can be seen that the Village Fund Allocation Management Planning (ADD) in the physical development of Gunung Gangsir Village, Beji District, Pasuruan Regency can be seen from the planning procedure that involves the community and community leaders being included in the planning, by providing authority to the community to provide ideas/thoughts to determine development, such as the construction of multipurpose buildings, axis roads, drainage, school fences, which prioritize the interests of the community first for the proper management of Village Fund Allocation (ADD). Accountability for the implementation of the ADD program to the government at the top level is carried out through a reporting system that is carried out periodically. accountability for the management of Village Fund Allocations in Gunung Gangsir Village, Beji District, Pasuruan Regency has been based on the principles of transparency and accountability. The administration of the Village Fund Allocation (ADD) management in the physical development of Gunung Gangsir Village, Beji District, Pasuruan Regency is based on government procedures and regulations. Every activity managed by the village government has recorded results so that ADD management can be carried out properly, and in accordance with the results of the planning and implementation activities that have been carried out. accountability for the management of the Village Fund Allocation (ADD) in the physical development of Gunung Gangsir Village, Beji District, Pasuruan Regency which is based on the results of the overall Village Fund Allocation (ADD) management activity, which can then be properly accounted for by the village government to the community.